(untitled) (Neliniini Kolyvannya, 2025)
We determine the solvability conditions and construct the general solution and the solution of the Cauchy problem for a system of linear inhomogeneous first-order differential equations with impulse action at fixed times and rectangular matrices in the system and impulses.